2016
DOI: 10.1155/2016/5093095
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy Suppresses Bone Cancer Pain through Inhibiting Activation of cAMP Signaling in Rat Dorsal Root Ganglion and Spinal Cord

Abstract: Radiotherapy is one of the major clinical approaches for treatment of bone cancer pain. Activation of cAMP-PKA signaling pathway plays important roles in bone cancer pain. Here, we examined the effects of radiotherapy on bone cancer pain and accompanying abnormal activation of cAMP-PKA signaling. Female Sprague-Dawley rats were used and received tumor cell implantation (TCI) in rat tibia (TCI cancer pain model). Some of the rats that previously received TCI treatment were treated with X-ray radiation (radiothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Repetitive spinal administration of the PKA inhibitor in early- and late- phases following TCI significantly delays or attenuates TCI-induced thermal hyperalgesia and mechanical allodynia. This provides direct evidence that activation of the cAMP-PKA pathway in DRG and spinal cord may mediate the development of bone cancer pain (Zhu et al, 2016). cAMP-dependent DRG neuron hyperexcitability (Huang et al, 2012) may be mediated by the phosphorylation of sodium and calcium channels (Rathee et al, 2002, England et al, 1996, Blackstone et al, 1994, Fraser and Scott, 1999).…”
Section: Activation Of Camp-pka and Cgmp-cgki Pathways In Drg And Thementioning
confidence: 87%
See 4 more Smart Citations
“…Repetitive spinal administration of the PKA inhibitor in early- and late- phases following TCI significantly delays or attenuates TCI-induced thermal hyperalgesia and mechanical allodynia. This provides direct evidence that activation of the cAMP-PKA pathway in DRG and spinal cord may mediate the development of bone cancer pain (Zhu et al, 2016). cAMP-dependent DRG neuron hyperexcitability (Huang et al, 2012) may be mediated by the phosphorylation of sodium and calcium channels (Rathee et al, 2002, England et al, 1996, Blackstone et al, 1994, Fraser and Scott, 1999).…”
Section: Activation Of Camp-pka and Cgmp-cgki Pathways In Drg And Thementioning
confidence: 87%
“…Activated cAMP-PKA pathway also promotes the synthesis of presynaptic neurotransmitters and vesicular transport by phosphorylating key transcription factors such as cAMP response element-binding protein (CREB) and synaptic vesicle proteins such as snapin (Koppert, 2004, King et al, 2005, Tumati et al, 2011). Studies have demonstrated the involvement of cAMP-PKA pathway in inflammatory pain (Malmberg et al, 1997, Hingtgen et al, 1995, Lewin and Walters, 1999), neuropathic pain (Song et al, 2006, Zheng et al, 2007, Huang et al, 2012) and bone cancer pain (Zhu et al, 2014, Zhu et al, 2016).…”
Section: Overview Of Camp-pka and Cgmp-pkg Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations